In vegetables... Seed production is a remunerative venture - Tomar, B S; Yalamalle, V R; Sharma, Rajesh Kumar (Indian Horticulture, 2019)
The vegetables are being cultivated by resource poor farmers and largely self-saved seed is being used by them, the contribution of hybrid seed is very less of total seed demand and limited to selected crops. The area under hybrid seed production is also very low. The seed production of hybrids is one of the means to meet ever increasing demand of quality seed of hybrids/varieties and offer several advantages such as earliness, uniformity, higher productivity, improved quality, resistance to biotic and abiotic stresses etc. and also provide quick and convenient way of combining desirable characters which make production more profitable than traditional/open pollinated varieties. Several hybrids/varieties have been released in vegetables in tomato, brinjal, chilli, cabbage, cucumber, bottle gourd, bitter gourd, watermelon, muskmelon, summer squash etc. Thus, production of genetically pure and quality seed by adopting suitable seed production techniques in remote areas where lack of developed vegetable market. Similarly, hybrid seed production on commercial scale is being done by hand emasculation and pollination. Hence, involvement of skilled labours resulting employment to rural youth and also producer fetches higher price of hybrid seed as compared to open-pollinated variety seed production and vis-Ã -vis commercial vegetable production.